The Impact of Government Debt, Expenditure and Taxes on Aggregate Investment and Productivity Growth. (April 2016) - Salotti, Simone; Trecroci, Carmine
Abstract : In this paper we evaluate empirically the impact of fiscal policy on two key determinants of long‐term growth, i.e., private investment and productivity growth. We mostly focus on a panel of 20 OECD economies from 1970 to 2009, although we also present some estimates based on data for 80 developing economies. Our findings suggest that high public debt adversely affects both aggregate investment spending and productivity growth, through distortions related to the size of the public sector. We also find weak evidence of some non‐linear effects on productivity, with government debt becoming more detrimental in advanced economies when above 85–90% of GDP.